Recessive null-allele variants in MAG associated with spastic ataxia, nystagmus, neuropathy, and dystonia - Zech, Michael; Brunet, Theresa; Škorvánek, Matej; Blaschek, Astrid; Vill, Katharina; Hanker, Britta; Hüning, Irina; Haň, Vladimír; Došekova, Petra; Gdovinová, Zuzana; Alhaddad, Bader; Berutti, Riccardo; et al. (Parkinsonism & related disorders, 2020)
INTRODUCTION: The gene encoding myelin-associated glycoprotein (MAG) has been implicated in autosomal-recessive spastic paraplegia type 75. To date, only four families with biallelic missense variants in MAG have been reported. The genotypic and phenotypic spectrum of MAG-associated disease awaits further elucidation. METHODS: Four unrelated patients with complex neurologic conditions underwent whole-exome sequencing within research or diagnostic settings. Following determination of the underlying genetic defects, in-depth phenotyping and literature review were performed. RESULTS: In all case subjects, we detected ultra-rare homozygous or compound heterozygous variants in MAG. The observed nonsense (c.693C > A [p.Tyr231*], c.980G > A [p.Trp327*], c.1126C > T [p.Gln376*], and 1522C > T [p.Arg508*]) and frameshift (c.517_521dupAGCTG [p.Trp174*]) alleles were predicted to result in premature termination of protein translation. Affected patients presented with variable combinations of psychomotor delay, ataxia, eye movement abnormalities, spasticity, dystonia, and neuropathic symptoms. Cerebellar signs, nystagmus, and pyramidal tract dysfunction emerged as unifying features in the majority of MAG-mutated individuals identified to date. CONCLUSIONS: Our study is the first to describe biallelic null variants in MAG, confirming that loss of myelin-associated glycoprotein causes severe infancy-onset disease with central and peripheral nervous system involvement.
Keywords: mutace; dospělí; dystonie; Genotype; Female; Spastic Paraplegia, Hereditary; Spinocerebellar Ataxias; dítě; předškolní dítě; spinocerebelární ataxie; spastická paraplegie dědičná; Pedigree; Adult; ženské pohlaví; dystonické poruchy; MAG; rodokmen; Dystonia; Dystonic Disorders; lidé; Myelin-Associated Glycoprotein; genotyp; Mutation; Intellectual Disability; Optic Atrophy; Muscle Spasticity; atrofie optického nervu; Male; Cerebellar Ataxia; Child, Preschool; glykoprotein asociovaný s myelinem; Spastic paraplegia; Ataxia; Child; mužské pohlaví; svalová spasticita; cerebelární ataxie; mentální retardace; Loss-of-function variants; Humans